Administrative Narratives, Human Rights, and Public Ethics: The Detroit Water-Shutoff Case. (3rd April 2017) - Ghere, Richard K.
Abstract : This inquiry focuses specifically on administrative (local official) narratives that speak to contentious issue contexts of social conflict. Specifically, it draws upon a theoretical connection between hermeneutics and the sociology of knowledge to interpret narrative passages of local officials and others related to a contentious public action—the Detroit Water and Sewerage District's stepped-up water-discontinuation efforts (2014 and 2015) that left thousands of inner-city residents with "delinquent" accounts and no access to water service. Selected narratives from this case are interpreted on the basis of their literary and social functions. The interpretations support a subsequent determination of whether and how the power and influence of administrative narrative assume significance as a matter of public ethics.